Predigtgottesdienst und Reformation Erwägungen zur Gottesdienstpraxis der Reformationszeit - Ferenc PAP (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2018)
Preaching Service and Reformation Considerations on Worship Practice of the Reformation.